Synthesis and rheological behavior of poly(1, 2-butylene oxide) based supramolecular architectures. Issue 8 (14th January 2016) - Allgaier, Jürgen; Hövelmann, Claas H.; Wei, Zhang; Staropoli, Mariapaola; Pyckhout-Hintzen, Wim; Lühmann, Nicole; Willbold, Sabine
Abstract : We describe the synthesis, analysis and rheological behavior of differently functionalized poly(1, 2-butylene oxide) based supramolecular polymers. Abstract : In this work we present the synthesis of poly(1, 2-butylene oxide) (PBO) functionalized with the complementary hydrogen bond forming groups 2, 4-diaminotriazine (DAT) and thymine. PBO is a rubbery polymer. Due to its semi-polar nature PBO is expected to suppresses non-directed cluster formation of the supramolecular groups but not influence their directed interactions. For the synthesis of backbone functionalized polymers we developed a procedure which allowed randomly copolymerizing BO with 1, 2-epoxy-7-octene using anionic ring opening polymerization with potassium tert -butanolate as initiator. The vinyl groups were converted to OH-groups by oxidation. In addition, PBO with one alcoholic end group was obtained by homopolymerization of BO. For the variant with OH-groups at both chain ends a procedure was developed which was based on the cleavage of the tert -butyl initiator group. In all the polymers the alcohol groups were basically quantitatively transformed into NH2 -groups. DAT and thymine functionalities were attached to the NH2 -groups again in almost quantitative conversion. All reaction steps were monitored by 1 H-NMR using pyridine-d5 as solvent. This method allowed determining the conversions of the different synthesis steps with high precision. The materials were examined in linear rheology in order to study the effect of the hydrogen-bonds on the dynamics of the resulting supramolecular structures. The results corroborate the exclusive existence of directed interactions between the supramolecular groups.